UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA SISWA SEKOLAH DASAR - Meysa Andriani; Febrina Dafit (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
In facing the challenges students face in reading, teachers need to be proactive in providing guidance to help them overcome obstacles that hinder the learning process. This research aims to explain the reading problems faced by students and the teachers' efforts to solve them in class II of SDN 002 Bagan Besar, Dumai City. The method applied in this research is a qualitative approach. Researchers used various data collection techniques including observation, interviews and document analysis involving research subjects consisting of class II B homeroom teachers and class II B students at SDN 002 Bagan Besar, Dumai City. The research results showed that there were class II B students who experienced difficulties in reading, such as lack of reading fluency, frequent mistakes, difficulty in distinguishing similar letters, and errors in pronouncing words or sound symbols. The efforts taken by teachers to overcome the reading difficulties of class II students at SDN 002 Bagan Besar, Dumai City, have been quite effective. Teachers use interesting and interactive learning methods, such as picture letter books, and strengthen students' self-confidence and motivation through praise. In addition, teachers do not blame students and provide special remedial programs to improve their reading skills